2021
DOI: 10.3390/ijerph18062948
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Psychoeducational Group Intervention Carried Out by Nurses for Patients with Depression and Physical Comorbidity in Primary Care: Randomized Clinical Trial

Abstract: The association between physical illness and depression implies a poorer management of chronic disease and a lower response to antidepressant treatments. Our study evaluates the effectiveness of a psychoeducational group intervention led by Primary Care (PC) nurses, aimed at patients of this kind. It is a randomized, multicenter clinical trial with intervention (IG) and control groups (CG), blind response variables, and a one year follow-up. The study included 380 patients ≥50 years of age from 18 PC teams. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(44 reference statements)
1
2
0
1
Order By: Relevance
“…The findings of this study are consistent with other Spanish RCTs on psychoeducational group interventions delivered by PHC nurses for people with depression and physical comorbidity ( 40 , 41 ). Furthermore, they are also consistent with a multidisciplinary online programmes that integrates evidence-based tactics from the fields of lifestyle medicine ( 42 ), as well as with a recent pilot RCT about a group-based lifestyle medicine for depression ( 43 ).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study are consistent with other Spanish RCTs on psychoeducational group interventions delivered by PHC nurses for people with depression and physical comorbidity ( 40 , 41 ). Furthermore, they are also consistent with a multidisciplinary online programmes that integrates evidence-based tactics from the fields of lifestyle medicine ( 42 ), as well as with a recent pilot RCT about a group-based lifestyle medicine for depression ( 43 ).…”
Section: Discussionsupporting
confidence: 91%
“…If we delve into the analysis of quality of life based on the EQ-5D scale variables, which is a tool that has been used in various studies that evaluate insomnia [75,77,78] and has been utilised to measure the results of cognitive behavioural and psychoeducational interventions [19,61,79], we have observed that some variables improve significantly, but not all. These variables are Pain/Discomfort (p = 0.016) and Self-Care (p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…This study forms part of a wider, multi-centre study in which 27 PCT from around Catalunya (Spain) took part (Raya-Tena et al, 2021). The PSICODEP study evaluated the efficacy of a psychoeducational group intervention conducted by PC nurses for individuals with depression and physical comorbidity.…”
Section: Context-the Psicodep Studymentioning
confidence: 99%
“…The qualitative research presented here is nested within the PSICODEP (psychoeducation, comorbidity, and depression) study, a clinical trial that obtained favourable results for depression remission and therapeutic response in individuals who presented both this condition and physical comorbidity. The participants received a psychoeducational group intervention given by previously trained PC nurses (Casañas et al, 2019; Raya‐Tena et al, 2021). Analysis of the data gathered from the nurses' diaries during the 12 intervention sessions, and their narratives regarding the individuals who attended them, can provide valuable information regarding dimensions not quantitatively researched.…”
Section: Introductionmentioning
confidence: 99%